E-LEARNING ACCESSIBILITY IN STATE-OWNED SCHOOLS IN NORTH BALI - Wicaksana Gede Dharma Arya; Dewi Ni Putu Febriana (Lingua Scientia, 2019)
This study aimed at investigating the implementation of e-learning in one of government non-favourite schools in Singaraja. This study was the result of the real implementationof e-learning in Bali in which the government expected e-learning to be applicable in every school in Bali since the launching of Balinese version of E-learning 2017. This research was a descriptive qualitative research. This study used snowball sampling in which the public opinion was counted. The data were collected by using observation and interview guide. The result of the study showed that the implementation of e-learning was not running well and became a serious problem. Some sollutions were offered in this study.